2018
DOI: 10.3389/fphar.2018.00771
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trajectories of Bromocriptine Antidiabetic Action: Leptin-IL-6/ JAK2/p-STAT3/SOCS3, p-IR/p-AKT/GLUT4, PPAR-γ/Adiponectin, Nrf2/PARP-1, and GLP-1

Abstract: Bromocriptine (BC), a sympatholytic dopaminergic D2 receptor agonist, has been comprehensively used in clinic to treat Parkinson’s disease (PD) and prolactinomas. Besides, BC represents a novel therapeutic option in type 2 diabetes (T2DM); however, the precise mechanisms are not completely unveiled. Hence, the objective of the current work is to clarify the potential molecular pathways of the insulin sensitizing effect of BC in the skeletal muscle of diabetic rats and to evaluate its possible interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
3
10
0
Order By: Relevance
“…The verified results were consistent with the RNA sequencing results. In agreement with literature reports, SOCS3, 35 , 36 OSM, 37 , 38 IL-6, 5 , 36 IL-10, 39 CXCL-1 5 and CXCL-8 17 increased significantly, so inflammatory factors-mediated injury is an important factor of BLI. OSMR and CDNK1A are the genes related to inflammatory response, cell growth and proliferation and involved in the JAK-STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…The verified results were consistent with the RNA sequencing results. In agreement with literature reports, SOCS3, 35 , 36 OSM, 37 , 38 IL-6, 5 , 36 IL-10, 39 CXCL-1 5 and CXCL-8 17 increased significantly, so inflammatory factors-mediated injury is an important factor of BLI. OSMR and CDNK1A are the genes related to inflammatory response, cell growth and proliferation and involved in the JAK-STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Vaspin was correlated with hsCRP and IL-6 in obese children, indicating that these factors are involved in the systemic inflammatory response. However, published data reported a negative correlation between vaspin and CRP, demonstrating that vaspin has anti-inflammatory and anti-atherosclerotic effects in the contexts of obesity-related inflammation and CVD [38, 39]. Therefore, the relationship between vaspin and inflammatory factors remains controversial and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the IL-6/JAK2/STAT3 pathway plays a critical role in the risk of pancreatitis-induced lung injury [15]. Meanwhile, the signaling pathway is also associated with the oxidative and inflammatory responses [16, 17].…”
Section: Introductionmentioning
confidence: 99%